Microgreens: An ultimate superfood - Yadav, Kalpana (Indian Horticulture, 2021)
Microgreens are the immature form of green leafy vegetables and can be harvested within 7-14 days including stem and leaves. They have an appealing appearance, soft texture, and powerful flavor, and supply a full pack of essential nutrients. Microgreens are usually more nutrient-rich than their mature counterparts. Concerning flavor acceptability, microgreens also have strong market acceptability. By exposing them to low temperatures with modified atmospheric packaging, consistency and quality can be preserved.